Case Report: Surgical management of medial collateral ligament calcification - You, Yihang; Li, Zhenhua; Guo, Jie; Zhang, Tao (Frontiers in Surgery, 2024)
Calcification is a self-limiting disease, characterized by the deposition of calcium, causing severe pain, swelling, and movement disorder. It is mainly found in the shoulder joint but has also been reported in other joints such as the wrist, hip, knee, foot, and ankle. However, calcification of the medial collateral ligament (MCL) has been rarely reported. The patient was a 47-year-old female without any trauma, whose chief complaint was pain and impaired flexion–extension of the affected knee joint. The diagnosis was calcification of the MCL, subsequently demonstrated by imaging examination. Conservative treatment was initially attempted, followed by arthroscopic surgery, and the postoperative pathological results confirmed the calcified tendon. The patient had a favorable prognosis 1 month after the procedure. This study demonstrates that arthroscopic surgery can result in effective and swift recovery of clinical outcomes for patients with calcification of the MCL.